The concise Oxford companion to English literature (Oxford Univ. Press, 1996)
Based on the vastly popular Oxford Companion to English Literature edited by Margaret Drabble, this indispensable volume offers over five thousand alphabetically arranged entries on individual novels, plays, songs, poems, novelists, poets, playwrights, essayists, philosophers, historians, fictional characters, literary movements, legends, and much more.